Challenges and opportunities in HIV pre-exposure prophylaxis use among women globally: A systematic review - Pradnyawati, Luh Gede; Wirawan, Ady; Januraga, Pande Putu (Science Midwifery, 2025)
Prevalence of HIV/AIDS remains high worldwide. Pre-exposure prophylaxis or PrEP is the use of an antiretroviral medication by HIV-negative people to reduce the risk of HIV acquisition. Ths systematic review aimed to analyse chalenge of hiv pre-exposure prophylactic use in low risk population. We conducted a search from the Scopus, Google Scholar, Science Directory and PubMed data bases. A total of 200 articles met the specified keywords, namely HIV, PreP, woman. In conclusion, PrEP is a highly effective HIV prevention tool for women when used consistently and as directed. Adherence, along with addressing behavioral, biological, and social factors, plays a crucial role in its effectiveness. Adherence to PrEP among women is influenced by a combination of factors related to healthcare access, support systems, individual perceptions, and daily routines. By addressing these factors and providing comprehensive support, healthcare providers can help maximize the effectiveness of PrEP in preventing HIV infection among women at risk. While HIV PrEP is highly effective when used correctly, the risk of drug resistance underscores the importance of regular monitoring, adherence support, and comprehensive counseling to maximize its effectiveness in HIV prevention efforts.